LEVERAGING AI IN HUMAN RESOURCE MANAGEMENT - PSNZ (Universiti Malaysia Terengganu, 2024)
Autonomic computing investigates how systems can achieve (user) specified ‘‘control’’ outcomes on their own, without the intervention of a human operator. Autonomic computing fundamentals have been substantially influenced by those of control theory for closed and open-loop systems. In practice, complex systems may exhibit a number of concurrent and inter-dependent control loops. Despite research into autonomic models for managing computer